2021
DOI: 10.3389/fpls.2021.658621
|View full text |Cite|
|
Sign up to set email alerts
|

Peanut Leaf Wilting Estimation From RGB Color Indices and Logistic Models

Abstract: Peanut (Arachis hypogaea L.) is an important crop for United States agriculture and worldwide. Low soil moisture is a major constraint for production in all peanut growing regions with negative effects on yield quantity and quality. Leaf wilting is a visual symptom of low moisture stress used in breeding to improve stress tolerance, but visual rating is slow when thousands of breeding lines are evaluated and can be subject to personnel scoring bias. Photogrammetry might be used instead. The objective of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 79 publications
(96 reference statements)
0
29
0
Order By: Relevance
“…These wavelengths were used in a previous report on wheat under drought stress by Moshou et al [65]. RGB color indices were reported recently to estimate peanut leaf wilting under drought stress [62]. To our knowledge, several other wavelengths identified in our study, including 242, 274, and 690 to 694 nm, have not been reported in other plant disease systems.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These wavelengths were used in a previous report on wheat under drought stress by Moshou et al [65]. RGB color indices were reported recently to estimate peanut leaf wilting under drought stress [62]. To our knowledge, several other wavelengths identified in our study, including 242, 274, and 690 to 694 nm, have not been reported in other plant disease systems.…”
Section: Discussionmentioning
confidence: 60%
“…Wilting of the foliage is a common symptom of peanut plants infected with A. rolfsii [4] and plants under low soil moisture/drought stress [60][61][62]. However, compared to the wilting of the entire plant caused by drought, the typical foliar symptom of peanut plants during the early stage of infection with A. rolfsii is the wilting of an individual lateral branch or main stem [4].…”
Section: Discussionmentioning
confidence: 99%
“…The visually rated scores were matched with the model derived scores, and two of the nearest scores (preceding and succeeding) of the visually rated scores were also matched. If any of the values (actual values, preceding or succeeding) matched with the model derived score, it was assumed as the correct classification ( Sarkar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In groundnut breeding, application of HTP methods to complement or replace traditional phenotyping is in incipient stages. Efforts have been put forward to develop HTP methods to assess leaf wilting ( Sarkar et al, 2021 ), plant height ( Yuan et al, 2019 ; Sarkar et al, 2020 ), and plant population and variety differentiation using RGB and NDVI ( Oakes and Balota, 2017 ). No HTP methods are yet available for phenotyping LLS and GRD resistance in groundnut.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, water loss due to transpiration is linked to plant biomass growth and yield ( Tanner and Sinclair, 1983 ; Blum, 2009 ). Low water availability reduces assimilate partitioning to reproductive sinks, and on a cellular level impairs cell growth and division ( Blum, 2011 ; Sarkar, 2020 ; Bennett et al, 2021 ; Sarkar et al, 2021a ). Water related stresses, such as direct drought stress and associated factors including high temperature and evaporative demand, reduce both transpiration and photosynthesis, resulting in reduced crop yield ( Sinclair, 2017 ; Balota et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%